2022
DOI: 10.3390/molecules27185891
|View full text |Cite
|
Sign up to set email alerts
|

An Alliance of Polynitrogen Heterocycles: Novel Energetic Tetrazinedioxide-Hydroxytetrazole-Based Materials

Abstract: Energetic materials constitute one of the most important subtypes of functional materials used for various applications. A promising approach for the construction of novel thermally stable high-energy materials is based on an assembly of polynitrogen biheterocyclic scaffolds. Herein, we report on the design and synthesis of a new series of high-nitrogen energetic salts comprising the C-C linked 6-aminotetrazinedioxide and hydroxytetrazole frameworks. Synthesized materials were thoroughly characterized by IR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…1,2 An integral part of this cycle involves chlorinated organic compounds (Cl org ), commonly utilized in chemical production elds such as the fabrication of energetic materials. [3][4][5][6] This process, however, invariably results in the generation of signicant volumes of chlorine-laden wastewater. The unregulated disposal of such wastewater poses severe threats to waterbodies and soil.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 An integral part of this cycle involves chlorinated organic compounds (Cl org ), commonly utilized in chemical production elds such as the fabrication of energetic materials. [3][4][5][6] This process, however, invariably results in the generation of signicant volumes of chlorine-laden wastewater. The unregulated disposal of such wastewater poses severe threats to waterbodies and soil.…”
Section: Introductionmentioning
confidence: 99%
“…Polynitrogen heterocycles have found their application in various fields of chemistry and material science, such as perspective high-energy density compounds [ 1 , 2 , 3 , 4 ], purine antimetabolites used in the treatment of cancer [ 5 ], chemosensors [ 6 ] and many others. In particular, pyrazolo [4,3- b ]pyridines are of considerable interest due to their diverse biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey showed that only salts 3a and 3b , as well as a salt 3 with 4-aminotriazole cation, 14 are known from the list of salts studied in this work. 2 N -Oxide isomers of salts 1 are considered in ref.…”
Section: Introductionmentioning
confidence: 99%
“…These ionic compounds are usually synthesized through scalable convenient procedures either upon direct neutralization of the corresponding acids or via a cation metathesis route. [11][12][13][14] As a rule, energetic salts have a high nitrogen content and do not exhibit corrosive properties, which ultimately results in their profoundly reduced hazardous nature. From the materials science point of view, the functional properties of energetic salts are easily modulated through a combination of different cations and anions or via a structural modification of ionic components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation